37% Phosphoric Acid Induced Stronger Matrix Metalloproteinase-8 Expression of the Dental Pulp than 19% Ethylene Diamine Tetraacetic Acid - Nadie Fatimatuzzahro; Tetiana Haniastuti; Juni Handajani (Journal of Tropical Life Science, 2014)
Etching agents such as ethylene diamine tetraacetic acid (EDTA) and phosphoric acid which are widely used in adhesive restoration system aimed to increase for retention of restorative materials, may act a chemical irritant that induce inflammation of dental pulp. Inflammation is a body response against irritant and infectious agents. Matrix metalloproteinase-8, the major collagenolytic enzyme, degrades collagen type 1. This enzyme is expressed in low level in normal condition, however, the expression will increase during inflammation. The purpose of the present research was to study the effect of 19% EDTA and 37% phosphoric acid application as an etching agents on the MMP-8 expression of dental pulp. Forty-five male Sprague Dawley rats were divided into 3 groups. Cavity preparation was made on the occlusal surface of maxillary first molar using a round diamond bur. 19% EDTA, 37% phosphoric acid, and distilled water were applied on the surface of the cavity of the teeth in group I, II, and III subsequently. The cavity then filed by glass ionomer cements. The rats were sacrified at 1, 3, 5, 7, and 14 days after the treatment (n=3 for each day). The specimens were then processed histologically. Immunohistochemical (IHC) analysis was performed using rabbit anti rat MMP-8 polyclonal antibody to examine MMP-8 expression and HE (Hematoxylen Eosin) staining to observe the number of macrophages. The results showed 37% phosphoric acid application induced stronger expression of MMP-8 and higher number of macrophages than 19% EDTA. The strongest expression of MMP-8 seems on 5 days after the treatment where the highest number of macrophages were also found.